CC(T) Specimen Load-Bearing Capacity Related to Yield Strength and Upper-Shelf Charpy-V Energy - Kim Wallin (Applied Mechanics, 2021)
The load-bearing capacity of a CC(T) specimen (Center-Cracked Tension) in the ductile fracture regime is usually controlled by plastic collapse. If the material’s tearing resistance is sufficiently low, the load-bearing capacity can drop below the plastic collapse value. Here, a recently developed simple fracture mechanics-based Charpy-V impact energy criterion for plastic collapse was used to provide a best estimate assessment of the CC(T) specimen load-bearing capacity.